Load Flow Based Voltage Stability Indices for Voltage Stability and Contingency Analysis for Optimal Location of STATCOM in Distribution Network with Integrated Distributed Generation Unit - Ibrahim Alhamrouni; M. A Alif; Bazilah Ismail; Mohamed Salem; Awang Jusoh; T. Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Electrical power system is growing rapidly with the current increasing demand. One of many important issues being faced in power system is the voltage instability. With that being said, this work investigates the voltage stability indices with contingency analysis used in order to determine the voltage stability of the network system. These approaches are used to detect and avoid voltage instability in the distribution network. The behavior of the distribution network is determined based on the contingency analysis. STATCOM is injected into selected buses in the distribution network of the system to determine the system’s stability during the contingency condition. Distributed generation (DG) is utilized to enhance the network stability. Different scenarios have been assumed in order to test the proposed technique under different conditions. The work has been implemented in Digsilent power factory environment. The proposed technique has been tested on IEEE 30 bus system. Promising results have been obtained with respect to previous published literature, in term of identifying the weak buses and enhancing the overall stability of the network.